Design of Active Analog Subwoofer Crossover Filter Linkwitz Riley 24 in Audio System - Hizkia, Dave Adonia; Suryadi, Dedy; Marindani, Elang Derdian (Faculty of Engineering, Universitas Tanjungpura, 2025)
The quality of an audio system is greatly influenced by the accuracy of frequency distribution, especially in the low-frequency range managed by the subwoofer. To achieve optimal separation, this study presents the design and implementation of a fourth-order active analog Linkwitz